Leptin Receptor (LEPR) promotes proliferation, migration, and invasion and inhibits apoptosis in hepatocellular carcinoma by regulating ANXA7 - Huang, He (Cancer Cell Int, 2021)
BACKGROUND: Leptin Receptor (LEPR) has been suggested to have several roles in cancer metastasis. However, the role of LEPR and its underlying mechanisms in lymphatic metastasis of hepatocarcinoma have not yet been studied. METHODS: We performed bioinformatics analysis, qRT-PCR, western blotting, immunohistochemistry, immunofluorescence, enzyme-linked immunosorbent, coimmunoprecipitation assays and a series of functional assays to investigate the roles of LEPR in hepatocellular carcinoma. RESULTS: We discovered that LEPR was highly expressed in liver cancer tissues, and the expression of LEPR in Hca-F cells was higher than that in Hca-P cells. Furthermore, LEPR promotes the proliferation, migration and invasion and inhibits the apoptosis of hepatocarcinoma lymphatic metastatic cells. Further studies indicated that LEPR interacts with ANXA7. Mechanistically, LEPR regulated ERK1/2 and JAK2/STAT3 expression via ANXA7 regulation. CONCLUSIONS: These findings unveiled a previously unappreciated role of LEPR in the regulation of lymphatic metastatic hepatocellular carcinoma, assigning ANXA7-LEPR as a promising therapeutic target for liver cancer treatments.